Do more overweight patients at admission lose weight during hospitalization? - Vieira Teles, Milena; Leandro Merhi, Vania Aparecida; Braga de Aquino, José Luiz; Teixeira Mendes, Elisa Donalisio; Mendonça, José Alexandre (Nutrición Clínica y Dietética Hospitalaria, 2020)
Aims: Investigate in-patients weight loss during hospital stay. Methods: In a retrospective study carried out with 170 inpatients, weight loss during hospitalization and its relationship with the type of disease, diet therapy, subjective global assessment (SGA), nutritional risk screening (NRS), anthropometry and hospitalization time (HT) were investigated. The Chi-square test, the Mann-Whitney and the univariate and multiple Cox regression analysis were used. Results: During hospitalization 41.18% patients experienced weight loss. Patients who were overweight experienced a higher rate of weight loss while in the ward (45.7% of patients; p=0.0179). Patients who were overweight, were twice as likely to lose weight during hospitalization, when compared with those who were already underweight (p= 0.0339; HR = 2.312; CI % = 1.066; 5.018). The age, gender, disease, diet prescribed during hospitalization, SGA, NRS, anthropometry and fasting time were not considered risk factors associated with weight loss. Conclusion: There was no influence of the dietary therapy type on weight loss. Only those patients who were overweight according to BMI were more associated to lose weight during hospitalization.